Phenotypic Detection of AmpC B-Lactamases in Gram Negative Bacteria - Karim, Fazlul; Rashid, Haxunur; Sattar, Abu Naser Ibne; Aluned, Sharmeen; Saleh, Ahmed Abu; Sattar, Huma]un; Miah, Md. Ruhul Amin (Bangladesh Journal of Medical Microbiology, 2016)
This study was carried out to detect AmpC f}-lactamase producing Gram-negative bacteria. A total of 374 bacterialisolates from primary cultures of wound swab (n:196) and urine (n:178) specimens collected from BSMMU andDMCH were investigated. Among the total 374 isolates, 344 (91.98o/o) were Gram-negative and 30 (8.027o) wereGram-positive bacteria. Majority of the Gram-negative bacterial isolates were Escherichia coli isolated from 160(46.520/0) of the cases followed by Pseudomonas species (74,19.79o ), Klebsiella species (4i2,l1.23oh), Enterobacterspecies (28,7.49o/o) and Enterococcus species (20, 5.35yo). All isolates were subjected to antimicrobial susceptibilitytest by Kirby-Bauer disc diffusion method and Gram-negative lst line-drug-resistant isolates were tested for AmpCf3-lactamase production by disc approximation test. Amon g 344 Gram-nrcgative bacteria isolated, 183(53.2%) were1st-line-drug-resistant of which AmpC fJ-lactamase was detected in 51 (27.8 7o/o) isolates.. The highest rate of AmpC Blactamase production was observed among Enterobacter spp. (5/10, 50o/o), followed by E. coli (23174,31o/o), Klebsiellaspp. (7127,25.92oh), Pseudomonas spp. (11145,24.44o/o), Acinetobacter spp. (3/15, 20r/o) and Proteus spp. (2112,16.670 ). Among individual samples,AmpC positive strains were found as the highest in isolates from urine (22/69,31.8870), closely followed by in burn wounds (30.88%) and surgical wounds (17.39oh). AmpC f3-lactamase producingE. coli was found as the highest in burn wounds (50o/o), Klebsiella spp. in urine samples (30.770 ), Pseudomonas spp.in burn. and surgical wounds (25oh), Enterobacter spp. in burn wounds (507o), and Acinetobacter spp. in urine(28.57oh). Proteus spp. was found only in burn wounds (22.22o/o). All AmpC f3-lactamase producers were sensitive toImipenem (100%). Considerable numbers of AmpC producing bacteria were detected from wound infection andurinary tract infection cases which indicate that AmpC is a major threat for antibiotic therapy. Bangladesh J Med Microbiol2008;02(01):28-32 DOI: http://dx.doi.org/10.3329/bjmm.v2i1.21930